2017
DOI: 10.1002/cncr.31204
|View full text |Cite
|
Sign up to set email alerts
|

Low testosterone at first prostate‐specific antigen failure and assessment of risk of death in men with unfavorable‐risk prostate cancer treated on prospective clinical trials

Abstract: Low, but not necessarily castrate, testosterone levels at the time of PSA failure confer a very poor prognosis. These observations provide evidence to support testosterone testing at the time of PSA failure. Given prolonged survival when abiraterone or docetaxel is added to ADT in men with castrate-sensitive metastatic PC and possibly localized high-risk PC provides a rationale supporting their use with ADT in men with low testosterone in the setting of a phase 2 trial. Cancer 2018;124:1383-90. © 2017 American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…These interventions could be implemented at a time before PSA failure, but when castrate resistance is suspected, based on a measurable PSA despite castrate levels of testosterone. 22 Therefore, in the current study, we investigate the prognostic significance of TTN, stratified by a detectable versus undetectable PSA nadir and adjusted for age, comorbidity, and known CaP prognostic factors, in men with newly diagnosed unfavorable risk prostate cancer using long term follow-up data from a randomized controlled trial that compared definitive radiation therapy (RT) with or without ADT. 23,24…”
Section: Introductionmentioning
confidence: 99%
“…These interventions could be implemented at a time before PSA failure, but when castrate resistance is suspected, based on a measurable PSA despite castrate levels of testosterone. 22 Therefore, in the current study, we investigate the prognostic significance of TTN, stratified by a detectable versus undetectable PSA nadir and adjusted for age, comorbidity, and known CaP prognostic factors, in men with newly diagnosed unfavorable risk prostate cancer using long term follow-up data from a randomized controlled trial that compared definitive radiation therapy (RT) with or without ADT. 23,24…”
Section: Introductionmentioning
confidence: 99%
“…After removing duplicates, 785 papers were screened and 40 full-text articles were selected and individually evaluated for eligibility. Finally, 19 studies were included for quantitative and qualitative analysis [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…An earlier investigation had previously shown that a low, but not necessarily castrate testosterone level at the time of PSA failure, 24 conferred a very poor prognosis 25 . However, it remains unclear whether the prognostic significance of PSAn and low testosterone at PSA failure is independent or overlapping.…”
Section: Introductionmentioning
confidence: 99%